지식재산 이러닝 교육프로그램 개발을 위한 직무분석 연구 - 이규녀; Kyu-nyo Lee; 박기문; Ki-moon Park; 하홍준; Hong-joon Ha (지식재산연구, 2014)
이 연구는 실제적 맥락에서 직무 중심 인재 양성과 더불어 지식재산 국가 핵심인재를 위하여 지식재산 이러닝 콘텐츠의 체계적이고 효율적인 관리 체제 구축의 토대를 마련하는 데 연구의 목적으로 두었으며, 연구 결과에 따른 결론은 다음과 같다. 첫째, 지식재산 분야의 직업세계에서 입직 초기에 수행 가능한 지식재산 인력의 직무능력 프로파일을 도출하였다. 41개 작업(entry level tasks)을 도출하여 4개 대영역, 9개 중영역으로 분류하였다. 둘째, 구안한 직무능력 프로파일에 대하여 설문조사, 전문가협의회 등의 연구 방법을 통하여 타당성과 신뢰성을 검증한 결과, 5개 대영역, 12개 중영역, 34개 능력요소로 분석되었다. 이는 지식재산 인력의 입직초기 작업들에서 도출된 것이므로 지식재산 이러닝 콘텐츠의 주제로 선정되어야 하며, 각 주제의 현황 및 내용 분석, 유지와 개선 및 폐기의 콘텐츠 평가체제 마련 등의 근거 데이터를 확보하는 준거로 활용될 수 있다. 셋째, 개발된 직무능력 프로파일에서 상대적으로 중요하면서 자주 수행되는 작업들을 우선적으로 신규 콘텐츠 또는 수정·보완 콘텐츠로 선정하여 유지·관리가 필요하다. 그 중에서 지식재산 권리화와 지식재산 창출은 중요도와 빈도가 상대적으로 높게 나타나, 이와 관련된 콘텐츠는 신규 개발이 필요할 뿐만 아니라, 콘텐츠의 세부적 평가에 따른 유지 관리가 시급하다. 결론적으로 능력을 중시하는 능력중심사회에서 지식재산 인재 양성을 위하여 지식재산 창출, 지식재산 권리화, 지식재산 보호, 지식재산 활용, 지식재산 경영 관련 직무를 기준으로 이러닝 콘텐츠의 현황과 내용을 분석하고, 직무의 중요도, 난이도, 빈도, 그리고 콘텐츠 평가 등 데이터 확보를 통한 지식재산 이러닝 콘텐츠 개발 방안이 마련되어야 한다. This study aims to provide foundations of systematic and efficient management system for intellectual property e-learning contents, which would help train talented individuals of job-oriented intellectual property. The results are as follows. First, 41 capability factors of job skills profile of intellectual property personnel were derived from entry level tasks and were divided by 9 middle areas and 4 large areas. Second, correction/modification of the job skills profile generated 5 large areas, 12 middle areas, and 34 capability factors after feasibility surveys, comparative analysis of the literature, and council with experts. These were derived from the entry level tasks of intellectual property personnel and should be selected as subjects of intellectual property elearning contents. In addition, they could be used as criteria for collecting relevant data in analyzing status and contents of each subject, and preparing contents evaluation system for maintenance, improvement and discard. Third, jobs that are relatively important in job skills profile and also frequently performed should be selected and maintained as new contents or correction/modification contents. Specifically, since creation of intellectual property and securing a right of intellectual property were shown to be such, new development of the relevant contents or maintenance according to contents evaluation results is urgently needed. In conclusion, analysis of status and content of e-learning contents and e-learning contents development plan through data collection including evaluation of importance, difficulty, frequency, and contents of job should be prepared in order to train talented individuals in intellectual property in this capability-oriented society based on creation of intellectual property, securing a right of intellectual property, protecting intellectual property, utilizing intellectual property, and intellectual property management-related jobs.